Strategic advertising management - Percy, Larry (Oxford University Press, 2001)
Strategic Advertising Management is a comprehensive book covering all areas of integrated marketing communications and combining rigorous empirical research with a wider perspective on the social and cultural aspects of advertising. Percy and Elliott deal with advertising from a strategic rather that simply a descriptive standpoint, starting out with a broad look at what advertising is meant to do and then going on to provide the reader with an understanding of what it takes to develop effective advertising and promotion. The book contains numerous examples of successful advertising images alongside accompanying commentary to illustrate just what goes into making an effective advertisement. There are also a number of extended advertising case studies which are used to illustrate the application of the various theories discussed and each chapter concludes with a number of empirical exercises and a range of discussion and essay questions.